The Use of ICT-Based Interactive Video to Enhance Students’ Engagement and Descriptive Writing Skills - Agustini, Sri; Heriyawati, Dwi Fita; Mustofa, Mutmainah (Journal of Foreign Language Teaching and Learning, 2000)
Writing skills are crucial in education, yet many students face challenges with engagement and interest. Given the increasing use of Information and Communication Technology (ICT) in education, exploring innovative approaches to address these issues is important. This study investigated ICT-based interactive video to enhance students' engagement and descriptive writing skills. Conducted with 33 seventh-grade students from a junior high school in Malang, this qualitative study employed classroom observations and analysis of written texts. Data analysis involved categorizing observation records by themes such as student engagement and interaction with the video. Students’ descriptive texts were examined for advancements in clarity, coherence, and creativity and categorized based on these aspects. The findings indicated that after using interactive videos, students’ descriptive writing displayed advancements in the three areas examined, with many students achieving high-quality levels. These results suggest that interactive videos can be a valuable tool for boosting students’ engagement and writing skills. The study highlights the need for incorporating such media into writing instruction. It suggests that further research should explore the refinement of these tools and their application in varied educational settings.